Transformations of form in the sculptures of the artist Burhan Saber - Karwan Rasheed Hasan (QALAAI ZANIST JOURNAL, 2019)
This research concerns the transformations of the form in the work of Burhan Sabir, and also seeks to determine these through s work.’some examples of the artist Transformations of form in the sculptures of the “ This research entitled is divided into four sections: ”artist Burhan Saber problematic of this search, The first part is about the definition of the its importance, its results, and its conceptual terminology. The second part is related to the theoretical framework, which is divided into two sections: the first section discusses the form and its importance in the value of - plastic art.the second section concerns the transformations of form in - contemporary art. The third part is devoted to the practical application of the research and s work ’it analysis a selected number of samples of the sculptor Burhan Sabir in order to determine the finalities of this research. The fourth part consists in the results obtained by the researcher s work, which are ’through the analysis of samples of Burhan Sabir summarized in three parts: 1-The sculptor Burhan Sabir realizes the change in his work, as a result of a simplification and rupture of the form of their realist origin, as shown in the samples analyzed. 2-The artist Burhan Sabir uses again the Sufi idea, through translating it into abstract forms as the major part of his creation. 3-The artist manages to transform the form by purifying some parts of the body and by abstracting other parts, in order to serve the subject and the expression, as we can see in the third sample.